IMPLEMENTASI PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK DI KOTA TASIKMALAYA - Andi . (UNIVERSITAS ISLAM SYEKH YUSUF, 2020)
The research aims to describe the process of procurement of goods and services electronically in the government of Tasikmalaya City. The method used is descriptive with a qualitative approach. Data collection techniques with interviews and observations of the website LPSE Tasikmalaya. Through the facility of the digital system, the process of procurement of goods and services electronically done openly, without interference or barriers and can be supervised by all stakeholders who have a sense of responsibility to the process is the best solution to answer the problems of procurement in the Government of Tasikmalaya. Administratively, the implementation of the procurement of goods and services electronically in the government of Tasikmalaya City has already been running legally and procedurally and the principles of procurement of goods and services electronically are efficient, effective, transparent, open, competitive, fair or not discriminatory, accountable or responsible have already been implemented well.